ANALISIS PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP MOTIVASI PEGAWAI PADA KOMISI PEMILIHAN UMUMKOTA MATARAM - Yusrin Yusrin (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2015)
This research was done to KPU Officers of Mataram City and aims to analyze theinfluencing variables toward work motivation that are leadership variable and workenvironment variable. This Research hypothesis was anticipated by a independent variableinfluencing by simultaneuosly and partially have an effect on to work motivation, andanticipated by a leadership variable have an effect on more dominant than work environmentvariable toward work motivation. This research use the appliance of data taken (instrument)in the form of questionaire laying open about leadership and work environment. So that datataken by good hence questionaire have to be up to standard of validity and reliability.Analysis technique used at this research is multiple linier regression analysis to know theaccurate independent variable influencing either through simultaneously and partially todependent variable. As for multiple linier regression model have to be up to standard ofpublic assumption of regression by conducting normality test heteroscedastisity test,multicolinearity test, and autocorrelation test. Pursuant to the result of F test analyze isproven by that independent variable in the form of leadership and work environment havethe influence which significant toward work motivation so that first hypothesis was accepted.While based on result of t test is proven by that independent variable by partially have aneffect on by significant toward dependent variable so that second hypothesis was accepted.Independent variable which is dominant influencing to the work motivation is leadershipvariable so that third hypothesis was accepted.Keywords : Leadership, Work Environment, and Motivation.